Amblysiphonella gradinarui n. sp. (Porifera) of Upper Triassic (Lacian 1-2) of the Vașcău Plateau (Romania) - Riedel, Peter; Senowbari-Daryan, Baba (Geologija, 1987)
While investigating the fossil assemblage of Upper Triassic limestones of the Colești Nappe (Vașcău Plateau, Romania) near Cîmp-Moți, a thalamid sponge characterized by a spongocoel consisting of about 200 tubes was found. The species described as Amblysiphonella gradinarui n. sp. occurs in Upper Triassic (Lacian 1-2) reef detritus limestones (Dachstein limestones).